1999
DOI: 10.1073/pnas.96.12.6902
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α is a key component in the obesity-linked elevation of plasminogen activator inhibitor 1

Abstract: Obesity is associated with a cluster of abnormalities, including hypertension, insulin resistance, hyperinsulinemia, and elevated levels of both plasminogen activator inhibitor 1 (PAI-1) and transforming growth factor ␤ (TGF-␤). Although these changes may increase the risk for accelerated atherosclerosis and fatal myocardial infarction, the underlying molecular mechanisms remain to be defined. Although tumor necrosis factor ␣ (TNF-␣) has been implicated in the insulin resistance associated with obesity, its ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
155
1
5

Year Published

2000
2000
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(175 citation statements)
references
References 54 publications
12
155
1
5
Order By: Relevance
“…TNF-␣ and TGF-␤ are potent inducers of PAI-1 expression, and in severe obesity a proportional increase in adipose tissue PAI-1 and TGF-␤ has been reported in humans and mice (25,26). It has been further suggested that increased TNF-␣ provides the common link between insulin resistance and elevated PAI-1 and TGF-␤ expression in obesity (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-␣ and TGF-␤ are potent inducers of PAI-1 expression, and in severe obesity a proportional increase in adipose tissue PAI-1 and TGF-␤ has been reported in humans and mice (25,26). It has been further suggested that increased TNF-␣ provides the common link between insulin resistance and elevated PAI-1 and TGF-␤ expression in obesity (26).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ and TGF-␤ are potent inducers of PAI-1 expression, and in severe obesity a proportional increase in adipose tissue PAI-1 and TGF-␤ has been reported in humans and mice (25,26). It has been further suggested that increased TNF-␣ provides the common link between insulin resistance and elevated PAI-1 and TGF-␤ expression in obesity (26). However, in adipocytes from FIRKO mice, PAI-1 and TGF-␤ gene expression were found to be up-regulated despite significantly lower TNF-␣ expression, suggesting that impaired insulin signaling can affect PAI-1 and TGF-␤ gene expression independently of increased TNF-␣ expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in adipocytes treated with TNF-␣, the IR accumulated less in the detergent-insoluble low-density membrane fractions (microdomains) and shifted to the high-density fractions, suggesting a translocation of IR from caveolar to noncaveolar fractions (40). TNF-␣ is a potent inducer of insulin resistance (41) and PAI-1 gene expression (42). It is chronically elevated in conditions of obesity and is a major culprit in the pathogenesis of obesity-driven insulin resistance (41).…”
Section: Discussionmentioning
confidence: 99%
“…18 We have also recently demonstrated that perivascular adipose tissue releases a factor that significantly modulates vascular response to constrictive stimuli. 19 In addition, obese individuals have high circulating plasma levels of a range of inflammatory markers and thrombogenic factors produced by adipose tissue including TNF-alpha, 20 interleukin-1 and fibrinogen. These factors, which can be reduced by weight loss, are likely to contribute to vascular damage in obese individuals.…”
Section: Adipose Tissue As An Endocrine Organmentioning
confidence: 99%